Penetration of Trichobilharzia cercariae into mammals: dangerous or negligible event? - Horák, P; Mikes, L; Rudolfová, J; Kolárová, L (Parasite (Paris, France), 2008)
Bird schistosomes and cases of human cercarial dermatitis occur worldwide, but the number of cases is not monitored. Experiments with two schistosomes, namely Trichobilharzia szidati and T. regenti, show that they possess potent tools to penetration bird and mammalian skin, as well as exhibit species-specific migration patterns within vertebrate bodies. Therefore, the infections may affect different organs/tissues e.g. lungs or spinal cord. In this minireview, the adaptations and pathogenic effects of bird schistosomes in experimental mammals are discussed, and some ideas/hypotheses on risks to humans from exposure to bird schistosome cercariae are expressed.
Keywords: Species Specificity; fyziologická adaptace; Lymnaea; Schistosomatidae; Animals; Trematode Infections; ptáci; Humans; Birds; druhová specificita; lidé; infekce červy třídy Trematoda; Lung Diseases, Parasitic; zvířata; Spinal Cord Diseases; nemoci míchy; parazitární onemocnění plic; Adaptation, Physiological